DISTRIBUTION AND POPULATION STATUS OF PUNJAB URIAL, OVIS VIGNEI PUNJABIENSIS (MAMMALIA: BOVIDAE), IN SOAN VALLEY, SALT RANGE, PUNJAB, PAKISTAN - W. A. Khan; M. S. Ahmed; A. Yaqub; H. Ali; M. Arshad (Journal of Animal and Plant Sciences, 2015)
A study on Punjab urial (Ovis vignei punjabiensis) was conducted in Soan valley during June 2011 to find out its distribution, population status and potential threats. Five potential sites namely: Dadder, Khabeki, Chambel, Kund and Uchali Forests were selected. The study conducted was based on Sample Count Technique, Line Transects and Point Counts methods as well as discussion with officials of Punjab Wildlife and Parks Department, representatives of local communities and local hunters. The occurrence of urial was confirmed at four out of five study sites. Using 17 transects and eight point surveys, 28% of the total area was sampled and 110 animals were estimated with a population density of 1.39 animals / km2. Male to female ratio was 1:1 while lamb to adult female ratio was 0.35:1. Questionnaire survey based on interviews of local residents including agriculturists, farmers, shepherds, livestock farmers, wildlife & forest officials, and local hunters was conducted for an assessment of the species occurrence and potential threats to the species. Signs such as fresh tracks, droppings and body parts including hair entangled with bushes, horns and other dead remains of the animal, as a result of natural or accidental deaths, were used as indication of the species presence in the study area. Habitat degradation due to increased developmental activities, poaching of lambs by local hunters, predation of lambs by continuously increasing population of jackals, illegal hunting due to weak enforcement of wildlife laws, intentional forest fire by local people to obtain firewood, food competition with livestock and transmission of various diseases from livestock to urial population were found as main threats to this species.
Keywords: Distribution range; population density; Punjab urial; salt range; Soan valley